PELATIHAN PENGEMBANGAN SOAL ASESMEN KOMPETENSI MINIMUM (AKM) BAGI GURU SMP NEGERI 8 MERAUKE - Abdul Rachman Taufik; Sadrack Luden Pagiling (LPPM Universitas Bina Bangsa, 2022)
This service aims to provide understanding and knowledge to teachers regarding the development of evaluation questions in the form of a Minimum Competency Assessment (AKM) in Merauke 8 Public Middle School. In this service activity carried out in several stages of activity including: Observation, Training and Assistance, Evaluation. The implementation of the activities carried out in two days of activities from 19 to 20 October 2022. Based on the results of the community service activities, positive responses were obtained from the training participants. This can be seen from the enthusiasm of the training participants where most of the participants took part in the activities from the initial stage to the final stage. In addition, this training can provide new knowledge and experience for trainees in developing AKM questions such as in determining stimulus, content, context, and cognitive level. The expectations of the training participants are that this training activity will continue with similar activities considering that most of the training participants have never received training, especially related to the National Assessment